The Effects of Work Environment, Work Discipline, and Work Motivation on Employee Performance - Herminingsih, Anik; Wiyoto, Valentino (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of work environment, work discipline, and motivation on employee performance at PT XYZ. The population in this study consisted of 400 employees of PT XYZ, with a sample size of 100 employees selected using simple random sampling techniques. Data collection was conducted using a survey method with a structured questionnaire distributed to the sample group. The data analysis employed descriptive analysis and was further processed using statistical tests to determine the relationships between the variables. The results of this study indicate that: (1) Work environment has a negative but non significant influence on employee performance. (2) Work discipline has a positive and significant influence on employee performance, (3) Motivation has a positive and significant influence on employee performance. These findings suggest that work motivation and work discipline are crucial for improving employee performance.